Influence of dehydration techniques on colour retention and related traits of gerbera (Gerbera hybrida) flowers - PINDER, ROHIT; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2018)
Gerbera (Gerbera hybrida) is the most popular florist flower due to various colours, shapes and sizes. It belongs to the family Asteraceae. The present study was conducted to determine the effect of different drying techniques on retention of flower colour and its related traits of Gerbera hybrida var. Doni. Maximum flower colour acceptability score (3.67), high acceptability of texture of dry flowers (3.67), minimum brittleness of dried flowers (2.33), minimum damage of florets (1.33) and maximum score (2.67) for the shape of embedded dry flowers were observed with vacuum air oven drying upto 60 days. Maximum colour retention up to 60 days was observed on the adaxial surface of the floret in vacuum drying (Y-O14A); however, on the abaxial surface of the floret, colour retention was seen maximum up to 60 days at room temperature drying, i.e. control (Y-12B) technique. Minimum reduction in flower size (5.22 %) was observed in vacuum drying; however, minimum reduction in flower weight (82.21%) was found in microwave drying technique. Vacuum air oven drying method was observed to be the best technique for retention of flower colour and related traits.